The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0004-282x2008000300021
|View full text |Cite
|
Sign up to set email alerts
|

Selective hypothermia: an experimental study on traumatic brain injury in rats

Abstract: -Objective:To evaluate the efficiency of selective hypothermia in the treatment of the traumatic brain injury in rats. Method: After the trauma produced for the model of cortical impact, a small craniectomy in the right frontoparietal region was carried through; after the procedure the animals had been divided in two groups of 15 each. Group A, without treatment with hypothermia (control group) and group B, treated with selective hypothermia for a period to 5 to 6 hours. After this time all the animals were sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Hypothermia has been evaluated under controlled conditions in various experimental methods of brain damage including TBI and temporary and permanent cerebral ischemia. [1][2][3]13,14 It has unequivocally been found to be a very potent neuroprotective method. However, hypothermia has not proven to be an overall benefit for patients affected by TBI in clinical studies because potentially protective effects were counteracted by systemic, particularly infectious, complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothermia has been evaluated under controlled conditions in various experimental methods of brain damage including TBI and temporary and permanent cerebral ischemia. [1][2][3]13,14 It has unequivocally been found to be a very potent neuroprotective method. However, hypothermia has not proven to be an overall benefit for patients affected by TBI in clinical studies because potentially protective effects were counteracted by systemic, particularly infectious, complications.…”
Section: Discussionmentioning
confidence: 99%
“…22 In small rodent models, surface cooling was reported to be especially effective for selectively lowering brain temperature after hemicraniectomy. 13,23 Forte et al found that surface cooling using ice packs led to a decrease of brain temperature from 37.1°C to 35.2°C in patients with a refractory elevation of ICP after hemicraniectomy. Unfortunately, the authors did not report the course of core temperature during the 12-hour cooling period.…”
Section: Discussionmentioning
confidence: 99%